Introduction to Statistics Through Resampling Methods and R. - Good, Phillip I. (Wiley, 2012)
Written in an informal, highly accessible style, this text is an excellent guide to descriptive statistics, estimation, testing hypotheses, and model building. It includes all the tools needed to facilitate quick learning, including: more than 250 exercises with selected hints, multiple explanations of basic concepts, real-life applications in client-, and statistics-related disciplines, a companion FTP site with data sets and R programs, and more.